2003
DOI: 10.1023/b:ejep.0000032353.03967.ef
|View full text |Cite
|
Sign up to set email alerts
|

Illicit Drug Use: Can it Predict Adherence to Antiretroviral Therapy?

Abstract: This study analysed the level of adherence to anti-HIV therapies in illegal drug users compared to non-users. Out of 214 patients interviewed. 60 (28%) reported current use of one or more illegal drugs (heroin, cocaine), alcohol (>6 U/day), psychoactive drugs and others. Within the two groups reporting use of heroin and cocaine, the percentage of patients achieving good levels of compliance was higher than among patients who reported not using any substance (50 and 46% vs. 42.3%), among the users of psychoacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 8 publications
2
10
0
1
Order By: Relevance
“…In contrast, Martini et al [38] found that heroin, cocaine, and alcohol users were not more likely to report nonadherence. In our data, alcohol use and crack use, but not recent injection drug use, were associated with nonadherence.…”
Section: Discussionmentioning
confidence: 88%
“…In contrast, Martini et al [38] found that heroin, cocaine, and alcohol users were not more likely to report nonadherence. In our data, alcohol use and crack use, but not recent injection drug use, were associated with nonadherence.…”
Section: Discussionmentioning
confidence: 88%
“…Esse mesmo autor encontrou associação significativa em dois outros artigos publicados em 2007. Em um desses artigos, escrito juntamente com Rosof e Mustanski, Parsons avaliou os subfatores do padrão de uso de álcool e demonstrou que entre os não aderentes é a quantidade de drinks consumidos pelo indivíduo que prediz se haverá ou não falhas na adesão [17][18][19][20][21] .…”
Section: Resultsunclassified
“…Six studies used a combination of adherence measurements, e.g., self-report and MEMS (Crystal et al 2001;Kerr et al 2005;Lucas et al 2001;Martini et al 2004;McNabb et al 2001;Roca et al 1999). …”
Section: Study Characteristicsmentioning
confidence: 99%